Accounting fraud: Case studies and practical implications - Henselmann, Klaus; Hofmann, Stefan (E. Schmidt, 2010)
Short description: In this casebook, with forty-four prominent examples drawn exclusively from real-world fraud cases, Klaus Henselmann and Stefan Hofmann provide comprehensive and crucial knowledge about the topic. With unparalleled insights on the scams used by corporate executives to perpetrate accounting fraud, in-depth coverage of the scandalous events at major corporations, an examination of the circumstances leading to these corporate governance fiascos and useful practice aids for fraud-fighters – including a schedule of early warning signs, an ``ethics barometer'', and an inquiry guide for fraud interviews. A must-read for anyone who cares about compliance and corporate integrity!; Country of final manufacture: DE Main description: language=eng>The number of high-profile accounting scandals is increasing. Accounting fraud is a real threat to modern business. In this casebook, with forty-four prominent examples drawn exclusively from real-world fraud cases, Klaus Henselmann and Stefan Hofmann provide comprehensive and crucial knowledge about the topic. The book is an invaluable resource to senior executives, financial officers, board members, audit committee members, auditors, attorneys, investors and many others. A must-read for anyone who cares about compliance and corporate integrity! Short description: language=eng>Systemvoraussetzungen: Internetzugang, Web-Browser, mobil: iOS und Android In this casebook, with forty-four prominent examples drawn exclusively from real-world fraud cases, Klaus Henselmann and Stefan Hofmann provide comprehensive and crucial knowledge about the topic. With unparalleled insights on the scams used by corporate executives to perpetrate accounting fraud, in-depth coverage of the scandalous events at major corporations, an examination of the circumstances leading to these corporate governance fiascos and useful practice aids for fraud-fighters – including a schedule of early warning signs, an ``ethics barometer'', and an inquiry guide for fraud interviews. A must-read for anyone who cares about compliance and corporate integrity!; Country of final manufacture: DE Main description: language=eng>The number of high-profile accounting scandals is increasing. Accounting fraud is a real threat to modern business. In this casebook, with forty-four prominent examples drawn exclusively from real-world fraud cases, Klaus Henselmann and Stefan Hofmann provide comprehensive and crucial knowledge about the topic. The book is an invaluable resource to senior executives, financial officers, board members, audit committee members, auditors, attorneys, investors and many others. A must-read for anyone who cares about compliance and corporate integrity! // ﻿ Short description: language=eng>Systemvoraussetzungen: Internetzugang, Web-Browser, mobil: iOS und Android In this casebook, with forty-four prominent examples drawn exclusively from real-world fraud cases, Klaus Henselmann and Stefan Hofmann provide comprehensive and crucial knowledge about the topic. With unparalleled insights on the scams used by corporate executives to perpetrate accounting fraud, in-depth coverage of the scandalous events at major corporations, an examination of the circumstances leading to these corporate governance fiascos and useful practice aids for fraud-fighters – including a schedule of early warning signs, an ``ethics barometer'', and an inquiry guide for fraud interviews. A must-read for anyone who cares about compliance and corporate integrity!; Country of final manufacture: DE Main description: language=eng>The number of high-profile accounting scandals is increasing. Accounting fraud is a real threat to modern business. In this casebook, with forty-four prominent examples drawn exclusively from real-world fraud cases, Klaus Henselmann and Stefan Hofmann provide comprehensive and crucial knowledge about the topic. The book is an invaluable resource to senior executives, financial officers, board members, audit committee members, auditors, attorneys, investors and many others. A must-read for anyone who cares about compliance and corporate integrit